Islam Jawa Kesalehan normatif versus kebatinan Mark R. Woodward ; penerjemah, Hairus Salim H.S. ; penyunting, Amirudin, Nuruddin. - WOODWARD, Mark R.; Hairus Salim HS; Amirudin; Nuruddin (LKis, 2012)
xxii, 410 hlm. 21 cm (3 eks.)